2014
DOI: 10.1007/5584_2014_49
|View full text |Cite
|
Sign up to set email alerts
|

Impulse Oscillometry in the Diagnosis of Airway Resistance in Chronic Obstructive Pulmonary Disease

Abstract: Spirometry is a standard lung function test for diagnosis and staging of chronic obstructive pulmonary disease (COPD). Impulse oscillometry (IOS) can be complementary to spirometry, especially in patients at advanced age and with physical or mental disorders who cannot be diagnosed through spirometry. The aim of this study was to compare IOS and spirometry in the assessment of airway obstruction in COPD. The study was conducted in 112 stable COPD patients, including 29 females and 83 males of the mean age of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…In all COPD subjects, R5–R20 had a stronger correlation with FVC, FEV 1 , FEV 1 /FVC, and MMEF ( r =−0.491, −0.628, −0.572, and −0.588, respectively) than X5 ( r =0.415, 0.561, 0.517, and 0.555, respectively). Piorunek et al18 showed that the severity of bronchial obstruction, as assessed by spirometry (FEV 1 %predicted), correlates with the measures obtained using the oscillometric method. The correlation between the FEV 1 %predicted and oscillometric measurements (R5, R5–R20, and X5) was significant ( r =−0.62, −0.80, and 0.75, respectively; P <0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In all COPD subjects, R5–R20 had a stronger correlation with FVC, FEV 1 , FEV 1 /FVC, and MMEF ( r =−0.491, −0.628, −0.572, and −0.588, respectively) than X5 ( r =0.415, 0.561, 0.517, and 0.555, respectively). Piorunek et al18 showed that the severity of bronchial obstruction, as assessed by spirometry (FEV 1 %predicted), correlates with the measures obtained using the oscillometric method. The correlation between the FEV 1 %predicted and oscillometric measurements (R5, R5–R20, and X5) was significant ( r =−0.62, −0.80, and 0.75, respectively; P <0.05).…”
Section: Discussionmentioning
confidence: 99%
“…(R5-R20)%R5 indicates the proportion of peripheral airway resistance to total airway resistance. [ 13 ] Reactance at 5 Hz (X5) relates to the physical properties of the lung parenchyma and its ability to expand and facilitate alveolar filling. Frequency response (Fres) is the point at which reactance is zero (when forces of inertia and capacitance are equal).…”
Section: Introductionmentioning
confidence: 99%
“…Fres and Ax are now considered sensitive indicators of reactive airflow limitation. [ 13 ] IOS parameters are more sensitive to bronchial provocation test, and bronchodilation test as compared to the traditional PFTs. [ 14 – 16 ] However, the relationship between IOS index and traditional PFTs, and the diagnostic role of IOS parameters in COPD patients on inhaled glucocorticoid or roflumilast therapy is not well-characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Определить реальные значения эластического и инерционного сопротивлений нельзя, но по их суммарной величине (компоненту Х) можно судить о преобладании того или другого сопротивления при разных частотах. Метод показал высокую информативность для диагностики и контроля лечения обструктивных заболеваний легких у взрослых и детей, бóльшую чувствительность в выявлении периферической обструкции дыхательных путей, чем спирометрия [19][20][21]. В единичных исследованиях метод форсированных осцилляций применяли для оценки влияния наркоза во время операций на механику дыхания [22,23].…”
Section: Introductionunclassified